2019
DOI: 10.5152/turkthoracj.2019.180203
|View full text |Cite
|
Sign up to set email alerts
|

Health hazards and complications associated with electronic cigarettes: a review

Abstract: Electronic cigarettes (ECs) are devices that vaporize and release a sweetened liquid containing nicotine as a substitute for burning tobacco. EC manufacturers have suggested that "vaping" is a safer alternative to conventional smoking because of the potential reduction of exposure to toxic substances. In 2019, National Youth Tobacco Survey reported that 10.5% and 27.5% of middle and high school students used ECs in the previous 30 days (0.6% and 1.5% in 2011, 3.3% and 11.7% in 2017, and 4.9% and 20.8 in 2018),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
1
3
0
1
Order By: Relevance
“…Noxious particles such as cigarette smoke can cause lung and systemic inflammation, including eosinophil activation; it is well known that cigarette smokers can develop acute eosinophilic pneumonia [45], while there is increasing recognition that inhalation of other products can also cause this [46,47]. In support of this argument, we found that current smokers had higher eosinophil counts, a phenomenon that was also observed in an Austrian general population study [25].…”
Section: Discussionsupporting
confidence: 83%
“…Noxious particles such as cigarette smoke can cause lung and systemic inflammation, including eosinophil activation; it is well known that cigarette smokers can develop acute eosinophilic pneumonia [45], while there is increasing recognition that inhalation of other products can also cause this [46,47]. In support of this argument, we found that current smokers had higher eosinophil counts, a phenomenon that was also observed in an Austrian general population study [25].…”
Section: Discussionsupporting
confidence: 83%
“…The e-cigarette, frequently viewed as a less harmful alternative to conventional cigarettes, has led to a significant shift in the tobacco market and industry in recent decades (Marques et al, 2021). The sudden escalation of e-cigarette usage among the youth can be associated with the widespread belief that ecigarettes are less detrimental given their absence of tobacco smoke and minimal nicotine content [47]. Although these tools are regarded as a safer alternative than conventional cigarettes, it should be emphasized that this does not signify that e-cigarettes are completely risk-free.…”
Section: The Hazards Of E-cigarettesmentioning
confidence: 99%
“…Recent reports have shown that e-cigarette use is not devoid of risk [ 21 ]. There is evidence of a similar or higher addictive potential of e-cigarettes compared to traditional smoking [ 8 , 22 ].…”
Section: Introductionmentioning
confidence: 99%